KOMIK DIGITAL BERBASIS CANVA SEBAGAI MEDIA PEMBELAJARAN YANG MENARIK PADA MATERI PERUBAHAN WUJUD BENDA - Humairah, Fitri; Asrul, Asrul; Rahayu, Desti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop a Canva-based digital comic as an engaging learning medium for the topic of changes in the states of matter in fifth-grade elementary school and to determine its feasibility and practicality. The research employed a Research and Development (R&D) method using the 4D model, including define, design, develop, and disseminate stages. The subjects were fifth- grade students of SD Muhammadiyah 2 Sorong City. Data were collected through expert validation sheets and teacher and student response questionnaires, then analyzed using a Likert scale converted into percentages. The results indicate that the developed digital comic is categorized as very feasible and very practical. The media is considered engaging because it combines illustrations, colors, and contextual storytelling that help students understand abstract scientific concepts more easily and enjoyably. Therefore, the Canva-based digital comic can be used as an innovative and relevant science learning medium in elementary schools.